Code Mixing and Code Switching in Twivortiare 2 Novel By Ika Natassa - Rizky Mirani Desi Pratama; Dwi Puji Hastuti (LPPM Universitas Bina Sarana Informatika, 2020)
The research aims to find the classification types of code switching and code mixing in twivortiare 2 novel then describe the influencing using types of code switching and code mixing in the novel. Descriptive qualitative method are used as the methodology in this research which means classify types of code switching and code mixing every sentences clearly through the dialogue of the novel. The research focused on the types of code switching (inter-sentential, intra-sentential, and tag-switching) and types of code mixing (insertion, alternation, and Congruent Lexicalization) while combine with influencing of used it. The results of the research many utterance are most of utterance using code mixing – insertation and code switching – intra-setential.